Photo‐Orientation Phenomena in Photochromic Liquid Crystalline Azobenzene‐Containing Polymethacrylates with Different Spacer Length. Issue 16 (23rd May 2017) - Bobrovsky, Alexey; Shibaev, Valery; Piryazev, Alexey; Anokhin, Denis V.; Ivanov, Dimitri A.; Sinitsyna, Olga; Hamplova, Vera; Kaspar, Miroslav; Bubnov, Alexej
Abstract : Two chiral liquid crystalline polymethacrylates with azobenzene‐containing side groups having different spacer length (6 and 10 methylene groups) are synthesized and studied. The correlations between spacer length, phase behavior, and photo‐optical properties are established and discussed. Abstract : Synthesis and investigation of the phase behavior and photo‐optical properties of two chiral liquid‐crystalline polymers with azobenzene‐containing side groups having different spacer lengths, 6 and 10 methylene groups (PMAzo‐6 andPMAzo‐10, respectively) are described. Formation of different smectic phases and high‐temperature cholesteric phase is studied by polarizing optical microscope, differential scanning calorimetry, and X‐ray investigations. It is shown that UV‐irradiation induces effective reversible E – Z photoisomerization in polymer solutions and films. Atomic force microscopy (AFM) study reveals substantial changes in the surface topography of the polymerPMAzo‐6 film after UV‐irradiation, whereasPMAzo‐10 surface remains the same. Irradiation by polarized light (457 nm) results in photo‐orientation process in polymer films consequential in significant alignment of the chromophores in direction perpendicular to the polarization plane of the incident light. A significant difference is found in thermal stability of the photoinduced alignment; an annealing ofPMAzo‐10 irradiated samples results in a slight decrease of dichroism values (down to 0.57); whereas the dichroism increases up to very high values (0.91) forPMAzo‐6 .